The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.toxrep.2016.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exposure to cadmium in sperm cells of zebrafish, Danio rerio

Abstract: Cadmium is a natural element found in the earth’s crust; it is usually associated with other metals, but due to the impacts caused by human activity, its concentration has increased in the aquatic environment. This metal may damage aquatic animal reproduction, decreasing the rate of fertilization of organisms such as fish. Thus, this study aimed to evaluate the in vitro toxicity of different concentrations of cadmium (0 (control), 0.5, 5, and 10 μg/L) using sperm cells of model organism zebrafish, Danio rerio.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 30 publications
(31 reference statements)
2
30
0
4
Order By: Relevance
“…The considerable variations in cadmium bioaccumulation may be the due to the difference in their feeding habits. Even cadmium concentrations of 5 and 10 g/L have harmful effects on reproduction, fertilization in aquatic animals [60] , [29] . Nurjanah et al [44] reported that the banana puffer fish from West Java having higher concentration of Cd in internal organs than skin and muscle.…”
Section: Resultsmentioning
confidence: 99%
“…The considerable variations in cadmium bioaccumulation may be the due to the difference in their feeding habits. Even cadmium concentrations of 5 and 10 g/L have harmful effects on reproduction, fertilization in aquatic animals [60] , [29] . Nurjanah et al [44] reported that the banana puffer fish from West Java having higher concentration of Cd in internal organs than skin and muscle.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, these metals are not only damaging to the adults but also highly nephrotoxic to newly born chicks [8] , affecting embryonic development [9] and causing renal and hematological toxicity [10] . In addition, these metals particularly Cd has been found to negatively affect the reproductive parameters of fish, reducing their fertility rate [11] . Therefore, there is a need to assess the level of these metals in the diet or preys consumed by the Milky stork as it has never been reported before.…”
Section: Introductionmentioning
confidence: 99%
“…A similar status was confirmed for Zn in human semen (Bassey et al, 2013), while this was not the case for Zn in common carp semen (Kovacik et al, 2018) and human semen (Vickram et al, 2013), and for Zn and Cu in bovine semen (Tvrdá et al, 2013). These differences are probably due to the individual characteristics of the species (Verma et al, 2009), the activity of male reproductive accessory organs (Alavi et al, 2004), and the metal pollution of water (Acosta et al, 2016). Finally, our results have shown that seminal plasma ions such as Na + , K + , Mg, and Ca 2+ were correlated with sperm cell velocities, while there is only the partially strong relationship between the VCL value and K + ion of sperm seminal plasma.…”
Section: Parameters Regression Equation Regression Squarementioning
confidence: 62%